Application Of The Discovery Method To Increase Mathematics Learning Compliance In Class Iia Students SD Negeri 0415 Huta Raja Lama T.P 2020/2021 - Syapina Rosya Harahap (STKIP Rokania Pasir Pangaraian, 2021)
This classroom action research was conducted at SD Negeri 0415 Huta Raja Lama in class IIA for the 2020/2021 academic year. Actions are taken by applying the discovery method to improve students' mathematics learning mastery. Discovery learning method is a learning method that can improve students' thinking skills to solve the problems they face. By using the discovery method, student learning completeness in each cycle changes and improves. This is evidenced by the achievement of pre-cycle test results, the average percentage is only 29.03% and at the end of the second cycle it reaches 87.10%. The application of the demonstration method can improve the competence of class II students SD Negeri 0415 Huta Raja Lama